Effectiveness of self-awareness training for young adults on improving their professional skills: a Quasi-experimental study - Venkatesh, Hemamalini; H. P., Jyothi; Kumar P. C., Pradeep (International Journal Of Community Medicine And Public Health, 2023)
Background: Young adulthood is a productive phase in an individual's life, marked by a shift towards achieving higher academic success and pursuing desired career paths. In this context, awareness of merits and demerits is vital in attaining desired goals. Therefore, the objective of the current study is to evaluate the differences in self-awareness skills among undergraduate students before and after participating in a life skills intervention program. Method: The study used a quasi-experimental design involving 243 students from four private undergraduate colleges. A half-day self-awareness training program was provided using activity-based participatory approaches. Data were collected pre and one-month post-intervention through a semi-structured questionnaire validated by two mental health professionals and three industry experts. Results: Of the 243 participants, 55.55% were female, and 44.44% were male. A significant number of female participants were in the age group of 18 to 20 (Male: 68 (62.96), Female: 113 (83.7), p<0.001) compared to male participants. The life skills intervention significantly enhanced participants' abilities to connect with like-minded individuals (Pre-in: 46.5%, post-in: 52.26%, p<0.01), make new friends (pre-in: 54.32%, post-in: 66.67%, p<0.002), and engage in team interaction (pre-in: 39.09%, post-in: 68.72%, p<0.001). additionally, there were improvements in adopting a positive approach towards tasks (pre-in: 62.14%, post-in: 64.2%, p<0.058) and prioritizing assignments (pre-in: 27.57%, post-in: 53.91%, p<0.001). Conclusions: Our study observed a significant improvement in the domains of harmony, self-belief, adaptability, and discipline post-intervention among students.